Anterior Skull Base Glomangioma-Induced Osteomalacia - Gresham, Malia S.; Shen, Steven; Zhang, Yi J.; Gallagher, Kelly (Journal of Neurological Surgery Reports, 2017)
Oncogenic osteomalacia (OO) is an uncommon but treatable cause of osteomalacia related to tumor production of FGF23, usually caused by benign mesenchymal neoplasms. Paranasal sinus glomangiomas are a rare cause of OO, with only one previously reported case. Here we describe a second case (first reported in English) of paranasal sinus glomangioma-induced osteomalacia in a 42-year-old man. He presented with weakness and multiple spontaneous fractures, and was found to have an ethmoid sinus glomangioma with intracranial extension. The tumor was removed via endoscopic endonasal approach to the anterior skull base, which resulted in complete resolution of symptoms and no further evidence of disease 1 year postoperatively.
Keywords: oncogenic osteomalacia; glomangioma; paranasal sinus tumor; glomus tumor